Propagation of Gembili (Dioscorea esculenta. L) Accession from West Papua by In-Vitro Callus Induction - Yuniardi Fifit; Dewi Ratna; Wahyudi Anung (E3S Web of Conferences, 2023)
Diversification of tuber foods is expected to help food security and improve public health. Gembili tuber glucomannan contains high fiber. Gembili seeds are becoming scarce, causing gembili plants to be very rarely found in the community. In the West Papua region, local people still rely on conventional supplies which are feared to threaten the gembili plant population. Tissue Culture Technology is very necessary in multiplying gembili seeds quickly and without knowing the season, by growing callus, plant propagation does not require a lot of explants to produce a large number of seeds. The research was conducted at the Politeknik Negeri Lampung Tissue Culture Laboratory, from May to July 2022. The research used a randomized block design, with each treatment repeated three times. The results showed that the composition of the media with the addition of 2.4 D 2 mL.L-1 produces an average of 8.00 days of callus growth, however, for callus growth the culture media with the addition of 2.4 D mL.L-1 produces a value best. 1.73 cm for callus diameter and a value of 0.22 g for callus weight.